MICROWAVE IRRADIATION AS AN ALTERNATIVE PROCESS FOR BIODIESEL PRODUCTION USING MACAUBA OIL (Acrocomia aculeata) - Marcos Roberto do Nascimento Pereira; Pedro Prates Valério; Salvador Carlos Grande; Maria Helena Caño de Andrade (The Journal of Engineering and Exact Sciences, 2016)
Macauba is an oleaginous palm tree widely found in Brazil. Its productive potential can reach 6000 kg of oil per hectare. In this study, crude vegetable oil was mechanically extracted from the mesocarp (pulp) of fresh Macauba fruit and subjected to physical-chemical determinations to analyse the following parameters: acid value, moisture content and kinematic viscosity. The results strongly indicate that Macauba palm oil is an alternative source of raw material for biodiesel production. Furthermore, concerning fatty acid composition, a predominance of unsaturated compounds was noted (75.92%) of which 63.21% are oleic acid, and 9.21% are linoleic acid. In this context, to produce ethyl esters, Macauba palm oil was subjected to alkaline transesterification by homogeneous catalysis, with microwave irradiation being applied to the heating step. The results indicated a conversion rate of 96.6%, for a molar ratio ethanol/oil of 12:1, a catalyst concentration equal to 1.0 wt% (KOH) and a reaction time equal to 60 seconds.